Газовыделение при повреждениях силовых трансформаторов и его ультразвуковая диагностика - Бирюлин, Владимир Иванович; Чернышев, Александр Савельевич; Горлов, Алексей Николаевич; Хорошилов, Николай Владимирович; Ларин, Олег Михайлович; Сергеев, Сергей Александрович; Куделина, Дарья Васильевна (НТУ "ХПИ", 2014)
В статье приведено решение проблемы газообразования при повреждениях силовых трансформаторов и его ультразвуковая диагностика. Основной целью исследования является выявление закономерности формирования газовых пузырей в масле при возникновении в трансформаторе перегревов. Предложенный метод обнаружения очага повреждений с помощью ультразвуковой локации является более эффективным способом, так как он позволяет существенно уменьшить время срабатывания защиты и повысить надежность защиты масляных трансформаторов.

This article contains the solution to the gassing problem in case of the power transformers damage and ultrasound diagnostics. The main purpose of the research is to identify the regularities of the gas bubbles formation in the oil in case of transformer overheating. The proposed method of damage detecting by ultrasonic locating is more efficient way as it allows to fix gases and bubbles and, respectively, overheating at earlier stage of their occurrence. As a result should be noted the following: first, the sound speed change in transformer oil indicates the initial moment of gassing, and thus enables to detect the occurrence of damage in the tank at the early stage. Secondly, the schematic diagram construction of the transformer protection may be based on the registration of the sound speed change or on the absorption of the sound waves at the start of gassing. A technical effect of the proposed method of the ultrasonic gas oil transformer protection is a significant decrease in the response time of protection and an increase of the oil transformers protection reliability.
Gassing at the damages of the power transformers and ultrasonic diagnostics
Keywords: силовой трансформатор; диагностика; повреждение; газовая защита; power transformer; diagnostics; damage; gas protection